The Effect of Islamic Maternal Parenting Style on Adolescent Aggressiveness by Modulating Peer Social Interaction - Alif Muarifah; Nurul Hidayati Rofiah; Fitriana Oktaviani; Mujidin Mujidin (Islamic Guidance and Counseling Journal, 2023)
The verbal and non-verbal aggressiveness of adolescents has been increasing. It is a form of aggression that involves hostile and coercive actions towards others that may result in emotional or physical harm. This study aims to examine the Islamic parenting style of mothers, the primary caregivers in Javanese culture in Indonesia, as well as the social interactions with peers in relation to aggressive behavior. The participants of this study were 410 high school students aged between 15 and 19 years old (M = 16.52, SD = 0.793), consisting of 210 male students and 200 female students. Participants were selected from eight schools in Sleman City (4 senior high schools and four vocational high schools). The data was collected using the aggression scale, maternal parenting style, and social interactions with peers. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with Smart-PLS 4. The study results show a good fit model, indicating that aggression is influenced by Islamic maternal parenting style with social interactions with peers as a mediator. Social interactions have a mediating effect on the relationship between Islamic maternal parenting style and adolescent aggression. Another finding reveals that each Islamic maternal parenting style negatively affects aggression. Adolescent aggression can be controlled through Islamic maternal parenting style (i.e., authoritarian, authoritative, and permissive) and peer social interaction as a mediator.